2011
DOI: 10.3892/or.2011.1497
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the invasion and migration of cancer cells by SERPINB family genes and their derived peptides

Abstract: Abstract.Apart from SERPINB2 and SERPINB5, the roles of the remaining 13 members of the human SERPINB family in cancer metastasis are still unknown. In the present study, we demonstrated that most of these genes are differentially expressed in tumor tissues compared to matched normal tissues from lung or breast cancer patients. Overexpression of each SERPINB gene effectively suppressed the invasiveness and motility of malignant cancer cells. Among all of the genes, the SERPINB1, SERPINB5 and SERPINB7 genes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 34 publications
2
58
0
Order By: Relevance
“…In addition, we found down-regulated expression of SERPINB5 in ILCs with respect to normal breast samples and to IDCs. It has been shown that SERPINB5 is a potent suppressor of the invasiveness and motility of malignant cancer cells [26,27], and our findings suggest a role for SERPINB5 in tumor invasion in ILCs.…”
Section: Discussionmentioning
confidence: 64%
“…In addition, we found down-regulated expression of SERPINB5 in ILCs with respect to normal breast samples and to IDCs. It has been shown that SERPINB5 is a potent suppressor of the invasiveness and motility of malignant cancer cells [26,27], and our findings suggest a role for SERPINB5 in tumor invasion in ILCs.…”
Section: Discussionmentioning
confidence: 64%
“…The two selected miRNA-21 targeted genes, PDCD4 and SERPINB5, have also been reported to play inhibitory roles in cancer cell invasion and migration [2, 13, 36]. To examine the influence of knockdown of miR-21 by anti-miR-21/R 8 complexes on cell migration, we used a wound-healing assay.…”
Section: Resultsmentioning
confidence: 99%
“…An important JUN target is the SERPINB5 (serpin peptidase inhibitor clade B, member 5), found also up-regulated upon DAC treatment in MCF7, and known as an important suppressor of the invasion and migration of cancer cells [68]. Then, another target is STAT5B (signal transducer and activator of transcription 5B), a member of the STAT family of TFs, normally activated in response to cytokines and growth factors signals.…”
Section: Resultsmentioning
confidence: 99%